2020
DOI: 10.1590/1980-0037.2020v22e65221
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the execution of core tactical principles and technical efficiency of primary school futsal players

Abstract: The study aimed to analyze the core tactical offensive principles and technical efficiency of primary school futsal players. Thirty-three students from a school in Paraná participated in the study. The System of Tactical Assessment in Soccer (FUT-SAT) and the System of Notational Analysis in Small-sided Soccer Games were used for tactical-technical analysis. It was found that the tactical principle “offensive coverage" was most frequently executed by the primary school futsal players (p = 0.01), followed by "w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
0
6
0
1
Order By: Relevance
“…Passing, dribbling, and shooting become the principles of futsal player performance. 14 This is seen in the research by 15 that the percentage of successful dribbling star and non star players were 39.06% and 37.67% respectively while the percentage of successful shooting star and non star players were 44.61% and 33.91% respectively and the percentage of successful passing star and non star players were 88.47% and 86.25% respectively. This proves the need of mastering futsal basic techniques, in which dribbling is one of them.…”
Section: Discussionmentioning
confidence: 89%
“…Passing, dribbling, and shooting become the principles of futsal player performance. 14 This is seen in the research by 15 that the percentage of successful dribbling star and non star players were 39.06% and 37.67% respectively while the percentage of successful shooting star and non star players were 44.61% and 33.91% respectively and the percentage of successful passing star and non star players were 88.47% and 86.25% respectively. This proves the need of mastering futsal basic techniques, in which dribbling is one of them.…”
Section: Discussionmentioning
confidence: 89%
“…Furthermore, the results found by Ueda et al [14] can be explained as the players who execute the 'offensive unit' are in areas of the court with less pressure from opponents, which favours the quality of the pass. In the present study, there was an association between the reception of the ball and efficiency in the tactical principle 'penetration'.…”
Section: Discussionmentioning
confidence: 95%
“…It may also indicate concern about the loss of ball possession, causing the players to position themselves in the rear, which is in line with the findings of Carneiro et al [27], who identified a greater number of balls recovered in the defensive sectors of the game. In this regard, Ueda et al [14] found that the young futsal practitioners who most frequently performed the 'offensive unit' principle were those who performed the pass with the highest quality. this principle consists of making movements of approach and support to the attack, building an offensive block that allows the team to add fluidity to the collective game [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A dinâmica coletiva de cooperação com os companheiros e de oposição com os adversários, juntamente com situações imprevisíveis, aleatórias e variáveis tornam o futsal um esporte com características complexas e sistêmicas (UEDA et al, 2020). Dessa forma, as interações entre os jogadores são essenciais para a continuidade do jogo e o desempenho nas partidas é norteado pelas principais fontes de informação sobre espaço e tempo que surgem entre atacantes e defensores (ALVES et al, 2022).…”
Section: Introductionunclassified